2009
DOI: 10.1016/j.bbrc.2009.01.012
|View full text |Cite
|
Sign up to set email alerts
|

SBF transcription factor complex positively regulates UV mutagenesis in Saccharomyces cerevisiae

Abstract: The collection of gene deletion mutants of Saccharomyces cerevisiae was used to screen for novel genes required for UV-induced mutagenesis. We found the SBF transcription factor (Swi4/Swi6 protein complex) to be required for wild-type levels of UV mutability in forward and reverse mutation assay. Expression of translesion polymerase ζ component Rev7 was identified as a target of SBFdependent regulation. KeywordsYeast; UV Radiation; Mutagenesis; Translesion synthesis; Transcriptional regulation Genetic instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…TLS pols were not identified near actively progressing replication forks in human cells, unlike all other components of the replisome, suggesting that TLS pols do not travel with progressing replication forks. , Indeed, pol η is distributed uniformly throughout the nucleus during unperturbed S-phase in human cells, in contrast to PCNA, which is concentrated into intranuclear foci at sites of DNA replication . Furthermore, the protein levels of TLS pols ζ and η in human and S. cerevisiae cells do not fluctuate significantly during the cell cycle nor in response to UV irradiation. , Collectively, this suggests that TLS on a UV-damaged Okazaki fragment most likely occurs after pol δ-mediated DNA synthesis has initiated from the nascent hybrid primer upstream (5′) of the offending damage.…”
Section: The Gps For Tls: Correlation Between Repriming the Damaged T...mentioning
confidence: 99%
“…TLS pols were not identified near actively progressing replication forks in human cells, unlike all other components of the replisome, suggesting that TLS pols do not travel with progressing replication forks. , Indeed, pol η is distributed uniformly throughout the nucleus during unperturbed S-phase in human cells, in contrast to PCNA, which is concentrated into intranuclear foci at sites of DNA replication . Furthermore, the protein levels of TLS pols ζ and η in human and S. cerevisiae cells do not fluctuate significantly during the cell cycle nor in response to UV irradiation. , Collectively, this suggests that TLS on a UV-damaged Okazaki fragment most likely occurs after pol δ-mediated DNA synthesis has initiated from the nascent hybrid primer upstream (5′) of the offending damage.…”
Section: The Gps For Tls: Correlation Between Repriming the Damaged T...mentioning
confidence: 99%
“…The commercially available collection of deletion mutants of non-essential genes of a haploid yeast strain (BY4741) was screened for strains with higher spontaneous mutation frequencies, using canavanine resistance as a forward mutation marker (Gong and Siede, 2009). While this screen was similar to the one described earlier by others (Huang et al, 2003), two novel genes were identified: SRL3 and TOP3 .…”
Section: Resultsmentioning
confidence: 99%
“…However, in swi6Δ cells, this repair pathway cannot be used effectively because DNA polymerase ζ does not function in these cells. The Rev7 protein, the regulatory subunit of DNA polymerase ζ, is barely detectable in swi6Δ (Gong and Siede, 2009). The shortage of the Rev7 protein and the resulting lack of DNA polymerase ζ activity are likely responsible for the extremely low mutation rate in swi6Δ (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the increased DNA rearrangement in cells lacking SWI6 is due to the accumulation of the recombinase Rad51 [a single-stranded (ss)DNA-binding protein responsible for homology searching during recombination (Sung, 1994)] and the diminished level of Srs2 (an Rad51 translocase), which together redirect DSB repair to an illegitimate recombination subpathway. This possibility is supported by the lower frequency of point mutations in the swi6Δ mutant than in the wild type (WT), likely due to Rev7 decay (Gong and Siede, 2009). Rev7 is a regulatory subunit of DNA polymerase ζ, which is responsible for most of the spontaneous mutations in haploid strains (Northam et al, 2010;Stone et al, 2012).…”
Section: Introductionmentioning
confidence: 99%